Inventory Planning Analysis (UMKM) of Angkringan D'amerta Business - Rohana, Siti; Sania; Pitriani; Syhartika Damayanti; Firly Amanda (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study discusses the analysis of inventory planning at Umkm Angkringan D'Amerta located in Cikarang Bekasi, owned by Ibnu Fadilah. Using data obtained from both internal and external sources, this study shows that the inventory planning used by Angkringan D'Amerta is relatively effective in managing the available food and beverages. The study's results also indicate that the inventory planning used by Angkringan D'Amerta can be improved by considering factors such as sales volume, raw material costs, and operational costs. Therefore, this study can contribute to the development of more effective and efficient inventory planning strategies for Angkringan D'Amerta and the food industry as a whole